Deindustrialization and Economic Growth: Empirical Evidence from Pakistan - Khan, Ghulam Yahya; Mehboob, Salik; Lopez, Lydia Bares (Asian Journal of Economic Modelling, 2018)
For the last four decades, ratio of services sector to economic growth has been increased among several developing countries. Like other developing economies Pakistan also experienced similar trends i.e. the share of services sector in Gross Domestic Product has expanded as compared to agriculture sector whereas manufacturing sector share remained stagnant. This situation is basically named as deindustrialization by some economists. In this context, present research tries to find out empirically the effects of deindustrialization on economic growth of Pakistan using time series data set ranging from 1972 to 2017. Auto Regressive Distributed Lag modelling technique has been used for estimation of the model. Empirical findings verified the fact that manufacturing value added has positive and significant impact on economic growth. The key finding suggested that Pakistan became a service economy without having proper experience of industrialization hence indicating deindustrialization in Pakistan. It is also concluded that Pakistan requires introducing such policies that encourage manufacturing sector growth as well as agriculture sector by curbing services sector. The study suggests that services sector should be prompted but not at the cost of manufacturing sector. This will render the growth journey of the country smoother and sustainable.